2007
DOI: 10.1128/mcb.02196-06
|View full text |Cite
|
Sign up to set email alerts
|

DNA Structure-Induced Recruitment and Activation of the Fanconi Anemia Pathway Protein FANCD2

Abstract: The Fanconi anemia (FA) pathway proteins are thought to be involved in the repair of irregular DNA structures including those encountered by the moving replication fork. However, the nature of the DNA structures that recruit and activate the FA proteins is not known. Because FA proteins function within an extended network of proteins, some of which are still unknown, we recently established cell-free assays in Xenopus laevis egg extracts to deconstruct the FA pathway in a fully replication-competent context. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 54 publications
4
51
0
Order By: Relevance
“…This result is consistent with the findings of Meetei et al (8) showing that in untreated human cells, FANCM exists as a phosphoprotein and is further phosphorylated in response to DNA damage. Moreover, our result supports the idea that the addition of circular plasmid to egg extracts at sufficiently high concentrations mimics the occurrence of DNA damage and triggers a DNA damage response that is uncoupled from ongoing replication (16).…”
Section: Resultssupporting
confidence: 75%
See 3 more Smart Citations
“…This result is consistent with the findings of Meetei et al (8) showing that in untreated human cells, FANCM exists as a phosphoprotein and is further phosphorylated in response to DNA damage. Moreover, our result supports the idea that the addition of circular plasmid to egg extracts at sufficiently high concentrations mimics the occurrence of DNA damage and triggers a DNA damage response that is uncoupled from ongoing replication (16).…”
Section: Resultssupporting
confidence: 75%
“…Using Xenopus egg extracts, we recently showed that although xFANCD2-Ub is recruited to chromatin in a replication-dependent manner, we can bypass the need for ongoing replication to trigger xFANCD2 monoubiquitination by adding dsDNA substrates, including circular double-stranded DNA (plasmid DNA), to egg extracts (16). We tested whether xFANCM is also modified in response to plasmid DNA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some researchers found that the FA complex might facilitate the recruitment of other proteins to maintain genomic integrity in the nucleus [37]. The mono-ubiquitinated form of FANCD2, as the central FA pathway protein, is essential for triggering the FA pathway [38]. Moreover, there is also evidence that FANCD2 interacts specifically with TNFR [35].…”
Section: Dan-jun Ma Et Al 657mentioning
confidence: 99%